Elite players` perceptions of football playing surfaces: A qualitative study - Roberts, J. R.; Osei-Owusu, P.; Mears, A. C.; Harland, A. R. (Research Quarterly for Exercise and Sport, 2020)
Purpose: The decision by the International Football Association Board in 2004 to approve the use of artificial surfaces in elite football (soccer) competitions remains controversial amongst many players, managers and coaching staff. The aim of this study was to conduct a comprehensive assessment of players` opinions to better understand the influence of playing surfaces on the game of football and identify factors that may contribute to differences of opinion. Method: Qualitative data were collected from 103 elite footballers and 21 coaching staff during a series of interviews and focus groups. A thematic analysis was conducted to identify patterns in the data. Results: Players considered that the type and condition of a playing surface influenced ball-surface interactions, game play, tactics/strategy, footwear selection, movement, risk of injury and fatigue. Together these influence a player`s perception of the suitability of a surface and also their mindset, which could ultimately affect their performance. Conclusion: The majority of participants in this study expressed a higher preference for natural grass over artificial turf pitches. A perceived increased risk of injury on artificial turf remains a primary concern despite a lack of supporting evidence in research studies. To address this discrepancy, the reporting of muscle soreness and the effect of constant surface switching merit further consideration. Not all participants shared the same views and player characteristics such as age, surface experience, injury history and playing style/position were found to be potential factors that could account for differences in elite players` opinions regarding the surfaces used in football.